Quality assessment of edible sesame oil samples produced in Jaffna District - Moganatharsa, G.; Vasantharuba, S.; Balakumar, S. (University of Jaffna, 2018)
Physico - chemical properties like relative density, moisture and other matter volatile, insoluble impurities, iodine value and unsaponifiable matter can be used to evaluate the quality of sesame oil. In this study ten sesame oil processing centers were selected randomly from seven divisional secretariats area in Jaffna district and two fresh samples of sesame oils were collected in two different time periods from these centers for quality analysis. All the laboratory analyses for sesame oils were done according to the Sri Lanka Standard (SLS) 313 procedure and the results were compared with Sri Lanka Standard 231:2013. According to the SLS 231:2013, the relative density ranges between 0.915-0.919, moisture and other matter volatile less than 0.2 percent by mass, insoluble impurities less than 0.05 percent by mass, iodine value ranges between 103-115 and unsaponifiable matter less than 1.5 percent by mass can be an indication for good quality sesame oil. The results of this study showed that the mean value of relative density and moisture content from eight and nine processing centers respectively were met the required SLS standard. Similarly the mean of iodine value and unsaponifiable matter of oils from seven out of ten processing centers were within the SLS standard value. But for the impurities only two out of ten processing centers met the SLS specification value. Samples obtained from five processing centers (50 %) contained the acceptable values for four out of five quality parameters. Results of this study show that most of the sesame oil processing centers available in Jaffna district need some modification or improvements in processing methods to meet all quality standards specified for sesame oil by SLS
Keywords: Iodine value; Insoluble impurities; Moisture content; Relative density; Unsaponifiable matter